Red light, green light - Suen, Anastasia; Wilson-Max, Ken (Orlando : Harcourt, 2005)
A young boy creates an imaginary world filled with zooming cars, flashing traffic lights, and racing fire engines.
"Gullivers Books."
Ages 2 to 5.
Keywords: Transportation -- Fiction; Motor vehicles -- Fiction; Traffic signs and signals -- Fiction; Stories in rhyme; Transportation -- Juvenile fiction; Motor vehicles -- Juvenile fiction; Traffic signs and signals -- Juvenile fiction